LQI-based adaptive super-twisting sliding mode controller for a pressurized water reactor in load-following operation - Hailemichael Guadie Mengsitu; Xiuchun Luan; Hetao Sun; Fabiano Gibson Daud Thulu; Muhammad Adnan (Annals of Nuclear Energy, 2026)

Molecular mechanisms and integrated breeding strategies for durable resistance to rice blast and other major pathogens - Daud Ali Shah; Muhammad Usama Younas; Zameer Hussain Jamali; Usman Zulfiqar; Mohammed S. Alotaibi; Mayank Anand Gururani; Owais Iqbal (Physiological and Molecular Plant Pathology, 2026)

AI and Multi-Omics for Climate-Resilient Remediation of Heavy Metal Soil Toxicity - Isma Gul; Muhammad Adil; Siqi Lu; Safdar Bashir; Heli Lu; Muhammad Daud; Younas Iqbal; Yu Tao (Water, Air, & Soil Pollution, 2026)

Phase-specific effects of guar meal and β-mannanase on growth performance and nutrient digestibility in broilers - Haroon Ur Rashid; Taimoor Khan; Muhammad Tahir; Muhammad Daud; Damiano Cavallini; Giovanni Buonaiuto (Tropical Animal Health and Production, 2026)
This study evaluated the phase-specific effects of dietary guar meal (GM) inclusion, with or without β-mannanase supplementation, on growth performance, nutrient digestibility, and energy utilization in broiler chickens. A total of 300 male Ross 308 broilers were assigned to eight experimental diets in a 4 × 2 factorial arrangement, consisting of four GM inclusion levels (0%, 4%, 8%, and 12%) with or without β-mannanase supplementation (0.35 g/kg), and were evaluated during the starter (7–21 d) and grower (22–35 d) phases. During the starter phase, broilers fed 4% GM supplemented with β-mannanase achieved growth performance comparable to the control diet, whereas increasing GM inclusion significantly reduced body weight gain, crude protein digestibility, and apparent metabolizable energy (AME; P < 0.05). β-mannanase supplementation partially alleviated these negative effects and fully restored crude protein digestibility at 4% GM. During the grower phase, broilers tolerated up to 8% GM without major reductions in growth performance, whereas 12% GM consistently impaired productive responses. Enzyme supplementation further enhanced body weight gain and protein digestibility across GM inclusion levels; however, its efficacy declined at 12% GM, where performance and energy utilization remained significantly lower than the control diet ( P < 0.05). These findings demonstrate that broiler responses to GM are strongly age-dependent and identify phase-specific tolerance thresholds for dietary inclusion. Under the conditions of this study, 4% GM during the starter phase and up to 8% GM during the grower phase can be successfully incorporated when supported by β-mannanase supplementation. This strategy may facilitate the sustainable utilization of guar meal as an agro-industrial by-product while maintaining productive performance and nutrient efficiency in broiler production systems.

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

State disaggregation for Non-Intrusive Load Monitoring (NILM) with calibrated bagged Seq2Point 1D convolutional neural networks - Md Mahadi Hasan Imran; Muhamad Zalani Daud; Muhammad Mukhtar Qureshi; Shahrizan Jamaludin; Atta-ur-Rahman; Md Meherullah; Abdullah Alqahtani (Energy and Buildings, 2026)

Physical and high-temperature rheological properties of asphalt binder incorporating waste engine oil modifier - Raza Mehmood; Fauzan Mohd Jakarni; Ratnasamy Muniandy; Salihudin Hassim; Nik Norsyahariati Nik Daud; Anwaar Hazoor Ansari; Zafreen Elahi; Muhammad Naveed (Innovative Infrastructure Solutions, 2026)

NMR-based metabolomics of Indonesian jamu for diabetes: chemical composition, toxicity, and zebrafish behavioral impact - Muhammad Safwan Ahamad Bustamam; Wimbuh Tri Widodo; Mohd Zuwairi Saiman; Siti Munirah Mohd. Faudzi; Siok Geok Chong; Nur Diana Safura Mohd Ezmir; Emelia Asmara Md Daud; Sonny Kristianto; Intan Safinar Ismail (Natural Product Research, 2026)

Integrating machine learning and deep learning for enhanced landslide susceptibility and propagation dynamics in Northwestern Pakistan - Hafiz Ullah; Wei Wang; Hamza Daud; Muhammad Afaq Hussain; Nafees Ali (Bulletin of Engineering Geology and the Environment, 2026)

Liquid organic hydrogen carriers (LOHC): from definitions to recent developments - Muhammad Usama Daud; Francesco Taddeo; Luciana Lisi; Ernesto Salzano; Martino Di Serio; Riccardo Tesser; Vincenzo Russo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Sadhan Kumar Ghosh and Sannidhya Kumar Ghosh. Circular economy adoption: catalysing decarbonisation through policy instruments - Muhammad Daud Bin Mahmud (Journal of Environmental Studies and Sciences, 2026)

Unveiling the impact of green technological innovation and foreign remittances on greenhouse gas emissions: A path to sustainable development in India - Muhammad Israr; Huaming Song; Arsalan Tanveer; Daud Abdul; Kashif Abbass (Environment, Development and Sustainability, 2026)

Navigating the asymmetric influence of smart grid technology, renewable energy and institutional quality toward a sustainable environment - Daud Abdul; Jiang Wenqi; Arsalan Tanveer; Muhammad Faheem (Environment, Development and Sustainability, 2025)

Evaluation of Neuroprotective and Neuroregenerative Potential of NeuroAiD™ II(MLC901) in a Rat Model of Kainic Acid-Induced Spinal Cord Injury - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Rashidah Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (Molecular Neurobiology, 2025)
Excitotoxic damage caused by high extracellular levels of glutamate in the spinal cord results in neuronal loss and severe locomotor impairment. This study investigates the efficacy of NeuroAiD II (MLC901), an herbal formulation, in promoting nerve regeneration following spinal cord injury (SCI) induced by kainic acid (KA). KA, a potent glutamate receptor agonist, causes excitotoxic damage in the spinal cord, leading to neuronal loss and locomotor impairment. To explore the potential of MLC901, KA-injured rats were treated with MLC901, and nerve regeneration was evaluated using various techniques. In this study, KA was administered intrathecally between the T12 and T13 vertebrae in rats, resulting in incomplete paraplegia. MLC901 was then tested for its neuro-regenerative potential. Various assessments were conducted to evaluate the effects of MLC901 treatment, including behavioral, electrophysiological, and histopathological analyses. Behavioral tests, such as the Basso, Beattie, and Bresnahan (BBB) open field test, running wheel, grid walk, inverted grid, and sensory tests, showed significant improvements in locomotor activity in treated rats. Electrophysiological recordings indicated that, while KA injection caused reduced amplitude and delayed latency, MLC901 treatment helped restore lost connections on days 14 and 28. Histopathological and immunohistochemical analyses also revealed improved tissue integrity and neuron survival. The study concludes that MLC901 significantly enhances locomotor recovery, somatosensory evoked potentials, and tissue preservation following SCI. These findings suggest that MLC901 holds promise as a neuro-regenerative therapy for spinal cord injuries.

Debris flow susceptibility and propagation modeling: a deep learning and flow-R framework - Muhammad Khalid; Muhammad Zulkarnain bin Abd Rahman; Jabir Hussain Syed; Nafees Ali; Hamza Daud; Muhammad Afaq Hussain; Muhammad Safwan Ruslan; Omar Farouk Fauzi (Bulletin of Engineering Geology and the Environment, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Advancing electrochemical water desalination: Machine learning-driven prediction and RSM optimization of activated carbon electrodes - Abdul Hai; Muhamad Fazly Abdul Patah; Muhammad Ashraf Sabri; G. Bharath; Fawzi Banat; Wan Mohd Ashri Wan Daud (Desalination, 2025)

The dynamic role of income inequality, renewable energy and risk components towards environmental sustainability: fresh insights through CS-ARDL approach - Muhammad Asif Khan; Daud Abdul; Wenping Wang; Arsalan Tanveer; Muhammad Faheem; Taimoor Hassan (Environment, Development and Sustainability, 2025)

A review of performance, mechanism, and challenges of layered double hydroxide-based biocomposites for the adsorptive removal of dye contaminants from water and wastewater - Salman Ahmad; Ghulam Mujtaba; Mukarram Zubair; Mansoor Ul Hassan Shah; Muhammad Daud; Nuhu Dalhat Mu'azu; Mamdouh A. Al-Harthi (Journal of Water Process Engineering, 2025)

Advanced AI approach for enhanced predictive modeling in reservoir characterization within complex geological environments - Wakeel Hussain; Muhammad Ali; Rakhshanda Sadaf; Harith F. Al-Khafaji; Izhar Sadiq; Chuanyu Hu; Hamza Daud; Salah Alshareef Alkfakey Ahmed (Modeling Earth Systems and Environment, 2024)

Markov chain quasi-Monte Carlo method for forecasting fire hotspots in Sarawak, Malaysia - Nurul Nnadiah Zakaria; Hanita Daud; Rajalingam Sokkalingam; Mahmod Othman; Evizal Abdul Kadir; Muhammad Naeim Mohd Aris; Noryanti Muhammad; Warih Maharani (Environmental Science and Pollution Research, 2024)

Jet fuel production via palm oil hydrodeoxygenation over bifunctional zeolite mixture supported Ni catalyst: Effect of Si/Al ratio - Saima Khan; Khan Muhammad Qureshi; Zeng Luyao; Andrew Ng Kay Lup; Muhamad Fazly Abdul Patah; Chong Yang Chuah; Wan Mohd Ashri Wan Daud (Biomass and Bioenergy, 2024)

Mechanical scratch injury on differentiated motor neuron of NSC-34 cells as an in vitro model for evaluation of neuroregeneration potential of NeuroAiD II (MLC901) - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (In vitro models, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Caring for the environment. How do deforestation, agricultural land, and urbanization degrade the environment? Fresh insight through the ARDL approach - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environment, Development and Sustainability, 2024)

Current progress on the computational methods for prediction of host-pathogen protein-protein interaction in the Ganoderma boninense-oil palm pathosystem - Mohamad Hazwan Fikri Khairi; Nor Azlan Nor Muhammad; Hamidun Bunawan; Kauthar Mohd Daud; Suhaila Sulaiman; Zeti-Azura Mohamed-Hussein; Mui-Yun Wong; Ahmad Bazli Ramzi (Physiological and Molecular Plant Pathology, 2024)

A holistic approach to embracing the United Nation's Sustainable Development Goal (SDG-6) towards water security in Pakistan - Ghulam Mujtaba; Mansoor Ul Hassan Shah; Abdul Hai; Muhammad Daud; Mazhar Hayat (Journal of Water Process Engineering, 2024)

Modelling of debris-flow susceptibility and propagation: a case study from Northwest Himalaya - Hamza Daud; Javed Iqbal Tanoli; Sardar Muhammad Asif; Muhammad Qasim; Muhammad Ali; Junaid Khan; Zahid Imran Bhatti; Ishtiaq Ahmad Khan Jadoon (Journal of Mountain Science, 2024)

Physiological and Metabolic Changes in Maize Seedlings in Response to Bisphenol A Stress - Haziq Hussain; Rehan Naeem; Baharullah Khattak; Zia ur Rehman; Niamat Khan; Muhammad Kamran Qureshi; Farah Deeba; Iftikhar Ali; Muhammad Daud Khan (Journal of Soil Science and Plant Nutrition, 2023)

Simultaneous adsorption of methylene blue and amoxicillin by starch-impregnated MgAl layered double hydroxide: Parametric optimization, isothermal studies and thermo-kinetic analysis - Ghulam Mujtaba; Asad Ullah; Danish Khattak; Mansoor Ul Hassan Shah; Muhammad Daud; Salman Ahmad; Abdul Hai; Faheem Ahmed; Thamraa Alshahrani; Fawzi Banat (Environmental Research, 2023)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

Assessment of heavy metals and associated oxidative stress in occupationally exposed workers from Bannu and Karak Districts in Pakistan - Kaleem Khan; Muhammad Tariq Rafiq; Aziz-Ur-Rahim Bacha; Iqra Nabi; Muhammad Irshad; Faridullah Faridullah; Muhammad Younas; Muhammad Daud Khan; Rukhsanda Aziz; Muhammad Amin; Awais Arifeen; Sohaib Aslam; et al. (Environmental Geochemistry and Health, 2023)

Construction of microbial electrodialysis cells equipped with internal proton migration pathways: Enhancement of wastewater treatment, desalination, and hydrogen production - Mohd Nur Ikhmal Salehmin; Muhammad Farhan Hil Me; Wan Ramli Wan Daud; Nazlina Haiza Mohd Yasin; Mimi Hani Abu Bakar; Abu Bakar Sulong; Swee Su Lim (Science of The Total Environment, 2023)

Effect of Different Solubilization pH Values on the Functional Properties of Protein Spirulina platensis Isolated Through Acidic Precipitation - N. A. Kamaruding; N. A. Muhammad Daud; N. Ismail; S. Shaharuddin (Journal of Aquatic Food Product Technology, 2022)

The roles of energy, natural resources, agriculture and regional integration on CO2 emissions in selected countries of ASEAN: does political constraint matter? - Muhammad Ibrahim Shah; Hauwah K. K. AbdulKareem; Balogun Daud Ishola; Shujaat Abbas (Environmental Science and Pollution Research, 2022)

The paradigms of transport energy consumption and technological innovation as a panacea for sustainable environment: is there any asymmetric association? - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environmental Science and Pollution Research, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

Screening of various Brassica species for phytoremediation of heavy metals-contaminated soil of Lakki Marwat, Pakistan - Iftikhar Ali; Muhammad Jamil Khan; Azizullah Shah; Farah Deeba; Haziq Hussain; Fazal Yazdan; Mati Ullah Khan; Muhammad Daud Khan (Environmental Science and Pollution Research, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Chromium (VI)-Induced Leaf-Based Differential Physiological, Metabolic and Microstructural Changes in Two Transgenic Cotton Cultivars (J208, Z905) and Their Hybrid Line (ZD14) - M. K. Daud; Shafaqat Ali; M. T. Variath; Mumtaz Khan; Muhammad Jamil; Maqsood Ahmad; S. J. Zhu (Journal of Plant Growth Regulation, 2022)

Multivariate geo-statistical perspective: evaluation of agricultural soil contaminated by industrial estate’s effluents - Muhammad Jamil; Ijaz Malook; Shafiq Ur Rehman; Muhammad Daud Khan; Muhammad Fayyaz; Muhammad Mudasar Aslam; Eui Shik Rha (Environmental Geochemistry and Health, 2022)

Unveiling the asymmetric impact of energy consumption on environmental mitigation in the manufacturing sector of Pakistan - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud; Saira Naseer (Environmental Science and Pollution Research, 2021)

Analysis of Shoreline Change Trends and Adaptation of Selangor Coastline, Using Landsat Satellite Data - Sunita Daud; Pozi Milow; Rozainah Muhammad Zakaria (Journal of the Indian Society of Remote Sensing, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Biochar impact on microbial population and elemental composition of red soil - Zabih Ullah; Shafaqat Ali; Niaz Muhammad; Naeem Khan; Muhammad Rizwan; Muhammad Daud Khan; Niamat Khan; Baharullah Khattak; Haifa Abdulaziz S. Alhaithloul; Mona H. Soliman; Hamid Ullah; Dilnaz Begum; et al. (Arabian Journal of Geosciences, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

Responses of morphological, physiological, and biochemical characteristics of maize (Zea mays L.) seedlings to atrazine stress - Shagufta Bibi; Sarzamin Khan; Nadia Taimur; Muhammad K. Daud; Azizullah Azizullah (Environmental Monitoring and Assessment, 2019)

Identifying a Gene Knockout Strategy Using a Hybrid of Simple Constrained Artificial Bee Colony Algorithm and Flux Balance Analysis to Enhance the Production of Succinate and Lactate in Escherichia Coli - Mei Kie Hon; Mohd Saberi Mohamad; Abdul Hakim Mohamed Salleh; Yee Wen Choon; Kauthar Mohd Daud; Muhammad Akmal Remli; Mohd Arfian Ismail; Sigeru Omatu; Richard O. Sinnott; Juan Manuel Corchado (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Sugarcane waste straw biochar and its effects on calcareous soil and agronomic traits of okra - Muhammad Riaz; Mumtaz Khan; Shafaqat Ali; Muhammad Daud Khan; Rehan Ahmad; Muhammad Jamil Khan; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Use of various biomarkers to explore the effects of GSM and GSM-like radiations on flowering plants - Muhammad Daud Khan; Shafaqat Ali; Azizullah Azizullah; Zhu Shuijin (Environmental Science and Pollution Research, 2018)

Pesticide-induced oxidative stress and antioxidant responses in tomato (Solanum lycopersicum) seedlings - Shakirullah Khan Shakir; Shahid Irfan; Basreen Akhtar; Shafiq ur Rehman; Muhammad Khan Daud; Nadia Taimur; Azizullah Azizullah (Ecotoxicology, 2018)

Ecotoxicological evaluation of two anti-dandruff hair shampoos using Lemna minor - Azizullah Azizullah; Shakirullah Khan Shakir; Shahana Shoaib; Halima Bangash; Nadia Taimur; Waheed Murad; Muhammad Khan Daud (Environmental Monitoring and Assessment, 2018)

Toward N-nitrosamines free water: Formation, prevention, and removal - Peter Adeniyi Alaba; Yahaya Muhammad Sani; Sunday Felix Olupinla; Wan Mohd Wan Daud; Isah Yakub Mohammed; Christopher C. Enweremadu; Olubunmi O. Ayodele (Critical Reviews in Environmental Science and Technology, 2017)

Modulation of Wnt signaling pathway by hepatitis B virus - Muhammad Daud; Muhammad Adeel Rana; Tayyab Husnain; Bushra Ijaz (Archives of Virology, 2017)

Satellite-sensed tropospheric NO 2 patterns and anomalies over Indus, Ganges, Brahmaputra, and Meghna river basins - Zia ul-Haq; Salman Tariq; Muhammad Ali; Asim Daud Rana; Khalid Mahmood (International Journal of Remote Sensing, 2017)

Mix cropping of legume (Vigna Radiata) and non-legume (Zea Mays) crops alleviates water stress as revealed by growth and biochemical parameters - Kalim Ullah Khan; Waheed Murad; Azizullah Azizullah; Hazir Rahman; Muhammad Daud Khan (Acta Physiologiae Plantarum, 2017)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Sulphur dioxide loadings over megacity Lahore (Pakistan) and adjoining region of Indo-Gangetic Basin - Zia ul-Haq; Salman Tariq; Muhammad Ali; Khalid Mahmood; Asim Daud Rana (International Journal of Remote Sensing, 2016)

Alleviation of lead-induced physiological, metabolic, and ultramorphological changes in leaves of upland cotton through glutathione - Mumtaz Khan; M. K. Daud; Ali Basharat; Muhammad Jamil Khan; Azizullah Azizullah; Niaz Muhammad; Noor Muhammad; Zia ur Rehman; Shui Jin Zhu (Environmental Science and Pollution Research, 2016)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

Impact of nanoparticles on human and environment: review of toxicity factors, exposures, control strategies, and future prospects - Muhammad Sajid; Muhammad Ilyas; Chanbasha Basheer; Madiha Tariq; Muhammad Daud; Nadeem Baig; Farrukh Shehzad (Environmental Science and Pollution Research, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

A study of aerosol properties over Lahore (Pakistan) by using AERONET data - Muhammad Ali; Salman Tariq; Khalid Mahmood; Asim Daud; Adila Batool; Zia-ul-Haq (Asia-Pacific Journal of Atmospheric Sciences, 2014)

A missense mutation (p.G274R) in gene ASPA causes Canavan disease in a Pakistani family - Rashida Hussain; Shakeela Daud; Naseebullah Kakar; Adeel Ahmad; Abdul Hameed Baloch; Abdul Malik Tareen; Muhammad Azam Kakar; Jamil Ahmad (Molecular Biology Reports, 2012)

An Alu repeat-mediated genomic GCNT2 deletion underlies congenital cataracts and adult i blood group - Guntram Borck; Naseebullah Kakar; Jochen Hoch; Katrin Friedrich; Jan Freudenberg; Gudrun Nürnberg; Rüstem Yilmaz; Shakeela Daud; Dost Muhammad Baloch; Peter Nürnberg; Johannes Oldenburg; Jamil Ahmad; et al. (Human Genetics, 2012)